NUMERICAL MODELING OF THE METAL CORD DISCHARGE PROCESS USING THE METHOD OF FINITE ELEMENTS - Yu. L. Bobarikin; M. N. Vereschagin; S. V. Avseykov; E. V. Shamanovskaya (Литьë и металлургия, 2012)
It reviews, that the use of FreeCooling technology at the JSC«BSW», will help to increase cooling capacity of equipment, to reduce energy costs, to extend the life of the cooling machine compressors, to increase the reliability of the existing cooling machines.